2006
DOI: 10.1080/02786820500466591
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Particulate Mass Emissions with the Electrical Low Pressure Impactor

Abstract: The electrical low pressure impactor (ELPI) is a useful tool for recording transient particle size distributions, such as in motor vehicle emissions. But for sub-micron aerosols, the straightforward mass weighting and integration of these size distributions overestimates the particulate matter (PM) mass by a factor of two or more. The present article examines the sources of this discrepancy and develops an analysis that allows quantitative PM mass measurement with an accuracy of about 20%. This procedure is ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
52
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(54 citation statements)
references
References 28 publications
2
52
0
Order By: Relevance
“…DPM particles are fractal-like agglomerates of approximately spherical 10-to 30-nm diameter primary particles with an effective mass density decreasing with decreasing particle size. 52,54 Pagels et al 36 demonstrated that charge-bearing nanoparticles deposit on the upper ELPI stages, thereby creating biases in these results. Zhu et al 55 implemented an ELPI fitting procedure 52 that accounts for these artifacts by iteratively adjusting the particle size and number concentrations for a bimodal distribution to match the current deposited on each impactor stage.…”
Section: Data Acquisitionmentioning
confidence: 99%
See 1 more Smart Citation
“…DPM particles are fractal-like agglomerates of approximately spherical 10-to 30-nm diameter primary particles with an effective mass density decreasing with decreasing particle size. 52,54 Pagels et al 36 demonstrated that charge-bearing nanoparticles deposit on the upper ELPI stages, thereby creating biases in these results. Zhu et al 55 implemented an ELPI fitting procedure 52 that accounts for these artifacts by iteratively adjusting the particle size and number concentrations for a bimodal distribution to match the current deposited on each impactor stage.…”
Section: Data Acquisitionmentioning
confidence: 99%
“…51 e C c ͑d m ͒d m 2 ϭ 0 C c ͑d a ͒d a 2 (2) where C c is the Cunningham correction coefficient and 0 the primary particle density, 2 g/m 3 . 52 Approximately 80 -90% of diesel particulate matter (DPM) mass is found in the 30-to 500-nm range. 53 ELPI software converts the current measured on each stage to PM mass assuming that particles are spherical with unit density and that d m ϭ d a .…”
Section: Data Acquisitionmentioning
confidence: 99%
“…Although aerodynamic distributions require no knowledge of particle density to obtain an accurate mass distribution, particle charging efficiency depends on particle mobility diameter and shape but not aerodynamic diameter, and thus the accuracy of the size distributions reported by the ELPI may vary depending on particle morphology. Considering these fundamental and other experimental uncertainties, Maricq et al (2006) estimated that the integration of aerodynamic size distributions using the ELPI yielded an uncertainty of about 20% in quantifying vehicle exhaust PM mass. Later, Dekati Ltd. developed the Dekati Mass Monitor (DMM) that, among other improvements for measuring engine exhaust, combines aerodynamic and mobility classifications to determine particle effective density in real-time by assuming a unimodal distribution (Lehmann et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Maricq et al (2006) reported the estimation of suspended PM mass using an Electrical Low Pressure Impactor (ELPI; Dekati Ltd., Kangasala, Finland). The EPLI measures real-time aerodynamic PSDs using cascade low-pressure impactors and electrometers at each stage.…”
Section: Introductionmentioning
confidence: 99%
“…The number concentration in each channel is calculated through the density-dependent charging law. Consequently, if the raw current distribution measured by the ELPI is not used, an assumption must be made on particle density (Maricq et al, 2006). Furthermore, the presence of multiple charged 5 particles at the outlet of the DMA, and consequently integrated into the ELPI signal, should be taken into account to avoid possible bias in estimation of particle effective density.…”
Section: Introductionmentioning
confidence: 99%